1989
DOI: 10.1111/j.1423-0410.1989.tb00815.x
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte‐Poor Platelet Concentrates at the Bedside by Filtration through Sepacell‐PL

Abstract: We developed a new filter, 'Sepacell-PL', consisting of a blood administration set for the preparation of leukocyte-poor platelet concentrates at the patient's bedside. This filter is packed with 1.8 microns polyester fibers coated with a new polymer, and has a volume of 14 ml. Sepacell-PL removed more than 99% of the leukocytes while approximately 93% of platelets were recovered from 10 units of platelet concentrates which contained 5 x 10(8) leukocytes and 3 x 10(11) platelets. The functions of pre- and post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

1990
1990
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 10 publications
1
12
1
Order By: Relevance
“…MPV was significantly reduced following filtration, which suggests that the filters can selec tively remove larger platelets. Similar results were reported by Miyamoto et al [18]; these findings can be considered a disadvantage, based on data indicating that larger platelets are younger and more effective, or an advantage, based on the opposite evidence that larger platelets are older and less hemostatically effective [20]. The results of studies con cerning platelet membrane expression of constituents asso ciated to platelet activation (GMP140 and gp 53) [7] and postransfusion recovery and survival (GMP 140 and gly coprotein lb) [4,6] indicate that filtration through these filters does not induce important modifications of the var iables examined.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…MPV was significantly reduced following filtration, which suggests that the filters can selec tively remove larger platelets. Similar results were reported by Miyamoto et al [18]; these findings can be considered a disadvantage, based on data indicating that larger platelets are younger and more effective, or an advantage, based on the opposite evidence that larger platelets are older and less hemostatically effective [20]. The results of studies con cerning platelet membrane expression of constituents asso ciated to platelet activation (GMP140 and gp 53) [7] and postransfusion recovery and survival (GMP 140 and gly coprotein lb) [4,6] indicate that filtration through these filters does not induce important modifications of the var iables examined.…”
Section: Discussionsupporting
confidence: 82%
“…This work is an extension to other studies which indicate that other parameters of platelet quality, i.e. pH [15,16], mor phology [16,17] and platelet function [15][16][17][18], are not signif icantly modified after platelet filtration. The results of our study indicate that leukocyte removal and platelet recovery are satisfactory with all three filters examined, although statistically significant variations in performance were found.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In this study we did not observe any signif icant difference in filtered platelets mean size compared to controls. These data differ from the results of other studies performed in our and other laboratories [5,15] on platelets suspended in plasma. The reason for this differ ence may be related to the synthetic medium used for BCPC storage in the present study.…”
Section: Discussioncontrasting
confidence: 57%
“…Recently, a sterile connection device has become available, and storage of pooled and/or fil tered platelet concentrates appears to be practicable. Al though a number of investigators reported in vitro charac teristics and in vivo effectiveness of filtered PC evaluated soon after filtration [2][3][4][5], studies on the feasibility of PC storage after filtration are scanty. Instead of using the traditional method of PC preparation from platelet-rich Materials and Methods bound fibrinogen, a kind gift of Dr. Budzynski (Philadelphia, Pa., USA).…”
Section: Introductionmentioning
confidence: 99%